PROGRAM KEMITRAAN MASYARAKAT PEMBERDAYAAN REMAJA MASJID DARUSSALAM DALAM MENINGKATKAN KESIAPSIAGAAN PRABENCANA PADA MASA PANDEMI COVID-19 DI DESA BUNUT WETAN KECAMATAN PAKIS KABUPATEN MALANG - Tavip Dwi Wahyuni; Tri Johan Agus Yuswantoro; Joko Pitoyo (Politeknik Kesehatan Kemenkes malang, 2022)
Indonesia is a country that is prone to disasters. In early 2021, a series of natural disasters hit Indonesia and claimed hundreds of lives. Starting from earthquakes, floods, tidal waves, landslides, to volcanic eruptions. During the Covid-19 pandemic, disasters will be felt more heavily by the community. Under these circumstances, the risk and transmission of diseases, especially Covid-19, increases. In dealing with disasters during the Covid-19 pandemic, community empowerment including the Darussalam Mosque Youth in Bunut Wetan Pakis Village must be carried out. The activities carried out are in the form of empowerment which is carried out for 3 days to determine the knowledge and skills of the Darussalam Mosque Youth community in Bunut Wetan Pakis Village. The results of the implementation of activities using test sheets were measured by pre-posting results, with an average pre-test score of 100% in the poor knowledge category, and an average post-test score of 100% in the good knowledge category. While the post-test results obtained 92% good knowledge category, while to be seen through the results before and before the show and the less than 100% category and after the demonstration increased to 100% good. There is an increase in knowledge and skills regarding Disaster Preparedness during the Pandemic Period. Training for Darussalam Mosque Youth is very much carried out, which can increase knowledge and understanding of disaster preparedness and preparation for disaster preparedness, and continue to use Health protocols, besides being able to educate families and surrounding communities from the results of the training